Poetical Parturition Objective Reading in creating innovative experiences at the old and modern poets - علي خليل شيرزاد (Al-Adab Journal, 2019)
Monetary seeks to shed light on the effects of literary order to detect reservoirs creativity, and taking the mystery substance initial configuration, and the interpretation of what could be behind it of secrets, and its surrounding the process of Temporal and spatial conditions .. and this ambition unbridled begun by the ancients and poets and critics, and they marched on their way Modern walkers on the path of their predecessors from the creators and scholars Even if ways are different and varied treatment methods and the nature of the consideration and handling. Aspiring this modest reading to stand at the first spark progress Which trigger in the mind of the poet creator, then to take the way into shape after suffering intractable, and bitter poetical parturition, to emerge from the whole process of the birth (poem) or poem project. Our reading tried as much as possible, examined the effects of labor poetic process when ancient and modern, from the monetary question follows How the poets process the poem in his mind? How many stages the process takes? Views of the parties: the ancient and the modernizers have been put forward, and I read an objective reading, between researcher and their own views in those views, as well as a statement of his own vision on the issue of various creative experiences.